The Effect of Pre-transplant Lipid Profile on Post-transplant Hepatocellular Carcinoma Recurrence: Retrospective Single-Center Analysis - İnce, Volkan; Carr, Brian I.; Usta, Sertaç; Ersan, Veysel; Bağ, Harika Gözükara; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2022)
Background: Plasma lipids have been shown to relate to tumor biology. We aimed to analyze the effect of pre-transplant plasma lipid profiles on post-transplant tumor recurrence in patients with hepatocellular carcinoma and to identify any possible relationship between the pre-transplant lipid profile with maximum tumor diameter, number of tumor nodules, tumor differentiation, portal vein invasion, or serum biomarker levels.Methods: Patients with hepatocellular carcinoma who underwent liver transplants between 2006 and 2021 had data collected pro- spectively and were analyzed retrospectively. Patients who did not have lipid profile data before transplant and whose post-transplant follow-up period was <90 days were excluded. Patients who had pre-transplant plasma lipid data and whose post-transplant follow-up period was >90 days were included in this study (n = 254).Results: Lower high-density lipoprotein cholesterol levels were found to be significantly associated with post-Tx recurrence (38 vs 29.5, P < .001) and were also significantly associated with macroscopic portal vein thrombosis (39 vs 30.4, P < .021). There was no significant association between plasma lipids and tumor differentiation. Higher high-density lipoprotein cholesterol levels were significantly asso- ciated with good overall and disease-free survivals (P = .024 and P = .001).Conclusion: Pre-transplant low plasma high-density lipoprotein cholesterol levels were significantly associated with portal vein throm- bosis and poor post-transplant overall and disease-free survivals.